Joint solder of lead free solder (Sn0.7Cu) and prrinted circuit board with various heat treatment temperatures. - Ariff Syakirin, Ghazalli (2007)
Soldering is used extensively in the electronic industry. It used to connect printed circuit board to join the circuit between electronic parts. The quality and reliability of electronic products strongly depend on those of solder joints. The quality reliability of solder joint as the title of this project is to study about joint solder of lead free solder (SnO.7Cu) and printed circuit board with various heat treatments. The objectives of this project is to analyze the strength between solder and printed circuit board by various heat treatment temperature besides investigate whether the change of temperature treatment will affect the joint strength of solder and printed circuit board. Tensile test is used in this project to analyze the reliability of the solder joint. At the end of the project, the reliable and efficient temperature is determined, 120°C at 1 hour heat treatment while unreliable temperature is 120°C at 2 hours of heat treatment.